Comparison of water saturation models based on well logging data : a case study of MX field in Malay Basin - Raja Johannes Raja Kamarul Shahrin,; Akhmal Sidek,; Augustine Agi,; Radzuan Junin,; Mohd Zaidi Jaafar,; Hariri Ariffin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
One of the primary methods to determine water saturation is logging measurement which uses water saturation models. Archie`s interpretation model to estimate water saturation in clean formations has successfully been useful over the years. However, in shaly sand formation this model yields inaccurate water saturation estimates due to shaly sand effects. Many shaly sand interpretation models have been developed; unfortunately; there is no unique water saturation model which works best for all formations as subsurface information may be limited and formation shaly sands may vary. Nevertheless, some water saturation models provide more accurate water saturation values for a formation. Thus, this study aimed to determine the water saturation alternative by using Dual-Water, Waxman-Smits, Indonesian, and Modified Simandoux models. The results showed that the Indonesian Model and Modified Simandoux gave the closest water saturation values with more than 80% similarities compared with logging analysis and thus should be considered the best models. Therefore, it is hoped that the findings can help improve knowledge on the selection of water saturation models best suited to the nature of formation similar to the wells, especially to other hydrocarbon exploration in the Malay Basin.